KAJIAN SIRKULASI ORANG DAN KENDARAAN DI AREA STASIUN TUGU YOGYAKARTA BERDASARKAN KONSEP âTODâ - , BUNI LUKITO HF ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tugu train station is a place that causing lot of attraction and generate the travel for the people that have been used the railway as their transportation mode. The railway user whether come and go to the Tugu station definitely need good media to help them go to the Tugu station. They are travelling in Tugu station area using many kind of modes such as using private vehicle, public transportation or by walking. Because of that reason, it should need a better controlling with a purpose to create a comfortable feeling in Tugu train station area. The used method in this research was descriptive quantitative which is explained the people circulation and vehicle especially Transjogja at Tugu train station area and estimated about the need of additional number of Transjogja that thru Tugu train station area and calculated the parking capacity in Tugu train station area. This research was conducted to understand Transit Oriented Development (TOD) concept in Tugu train station area. The function from this TOD concept is to find out the potential demand of using public transportation (Transjogja) and know the additional number of Transjogja, the perform of parking capacity in Tugu train station and synergized in modes transfer at the Tugu train station area. TOD concept in Tugu train station area is analyzed the travel demand that been needed in public transportation in this case focused in parking analyze in that area. The conclusion from this study with an aplication of TOD concept that in Tugu train station still needed a good parking management. There are two alternatives that can be suggest as guidelines in parking management. Each alternatives has an advantages and disadvantages.